Ultrasensitive Photoresponsive Devices Based on Graphene/BiI3 van der Waals Epitaxial Heterostructures. (17th April 2018) - Chang, Po‐Han; Li, Chia‐Shuo; Fu, Fang‐Yu; Huang, Kuo‐You; Chou, Ang‐Sheng; Wu, Chih‐I
Abstract: In recent years, bismuth iodide (BiI3 ), a layered metal halide semiconducting light absorber with a wide bandgap of ≈1.8 eV and strong optical absorption in the visible region, has received greater attention for photovoltaic applications. In this study, ultrasensitive visible‐light photodetectors with graphene/BiI3 vertical heterostructures are achieved by van der Waals epitaxies. The BiI3 films deposited on graphene show flatter morphologies and significantly better crystallinities than that of BiI3 films on SiO2 substrates, mainly due to weak van der Waals interactions at the graphene/BiI3 interface. Hybrid photodetectors with highly crystalline graphene/BiI3 heterostructures demonstrate an ultrahigh responsivity of 6 × 10 6 A W −1, shot‐noise‐limited detectivity of 7 × 10 14 Jones, and a relatively short response time of ≈8 ms. Compared to most previously reported graphene‐based hybrid photodetectors, these devices have comparable photosensitivities but a faster response speed and lower operation voltage, which is quite promising for ultralow intensity visible‐light sensors. Moreover, the electronic structure and interfacial chemistry at the graphene/BiI3 heterojunctions are investigated using photoemission spectroscopy. The results give clear evidence that no chemical interactions occur between graphene and BiI3, resulting in the van der Waals epitaxial growth, and the measured band bending consistently illustrates that a photoinduced charge transfer occurs at the graphene/BiI3 interface. Abstract : High‐quality crystal growth of layered metal halide BiI3 is demonstrated using van der Waals epitaxies. Compared to BiI3 on SiO2, BiI3 films on graphene produce flatter morphologies and remarkably better crystallinities because of weak van der Waals interactions at the graphene/BiI3 interface. The electronic structures and band bending at the graphene/BiI3 heterojunctions are also investigated using photoemission spectroscopy.